The role of sensory attenuation in symptomatic and healthy individuals: a scoping review - Rossi, Luca; Cerritelli, Francesco; Thacker, Mick; Esteves, Jorge E. (Frontiers in Neuroscience, 2025)
BackgroundPersistent physical symptoms (PPS), including functional neurological disorders (FND), chronic pain, and other neurological conditions [e.g., Parkinson’s disease (PD), Huntington’s disease (HD), autism spectrum disorder (ASD), and psychosis], present substantial challenges for healthcare systems due to their complex and multifaceted nature. These disorders often involve maladaptive sensory processing and heightened sensory perception, contributing to disability and psychological distress. Sensory attenuation (SA) is a neurophysiological mechanism that helps differentiate self-generated from external sensory stimuli, filtering irrelevant sensory input. Altered SA has been implicated in the pathophysiology of FND, chronic pain, and PPS, where impaired sensory modulation contributes to symptom persistence.AimsThis scoping review aimed to explore the role of SA in healthy individuals and those with FND, neurological disorders, and chronic pain. A secondary objective was to examine SA measurement techniques and their clinical relevance.MethodsFollowing the Joanna Briggs Institute (JBI) methodology and PRISMA-ScR guidelines, a comprehensive search of PubMed, ScienceDirect, and Google Scholar identified studies published between 2013 and 2023. Inclusion criteria encompassed investigations of SA in both symptomatic and healthy populations, focusing on FND, neurological disorders, and chronic pain. Data extraction highlighted SA mechanisms, assessment methods, and clinical implications for manual therapy and musculoskeletal (MSK) care.ResultsA total of 62 studies involving 3,344 participants were included. Findings indicated that SA is essential for sensorimotor integration and the sense of agency in healthy individuals. However, disruptions in SA were consistently observed in FND, chronic pain, and neurological disorders, leading to sensory hypersensitivity, impaired motor control, and a distorted sense of agency. SA was assessed using methods such as the force-matching paradigm, electroencephalography (EEG), event-related potentials (ERPs), and functional magnetic resonance imaging (fMRI), providing insights into neurophysiological alterations.ConclusionThis review highlights the critical role of SA in adaptive sensory processing and its disruption in conditions like FND and chronic pain. Integrating SA-based interventions, such as sensorimotor retraining and affective touch, into manual therapy and MSK care may help recalibrate sensory processing and improve patient outcomes. Future research should focus on standardizing SA assessments and exploring its modulation in clinical settings to enhance person-centered therapeutic approaches.